Chemotherapy Induced Neutropenic Fever and Its Response to Empirical Antimicrobial Therapy - Murtaza, Hafiz Muhammad; Maryam, Samra; Iqbal, Muhammad Shaheen; Ghafoor, Tariq; Awan, Aamir Aslam; Farid, Naeem (Pakistan Armed Forces Medical Journal, 2022)
Objective: To find out the frequency of chemotherapy-induced febrile neutropenia (FN) in children diagnosed with Acute Lymphoblastic Leukemia (ALL) and its response to empirical antibiotic therapy. Study Design: Cross-sectional study. Place and Duration of Study: Department of Peadiatric Oncology, Combined Military Hospital, Rawalpindi Pakistan, from Nov 2017 to Oct 2018. Methodology: Newly diagnosed pediatric patients suffering from acute lymphoblastic leukemia between 1 to 15 years of age were included. All patients were treated with chemotherapy according to the United Kingdom National Randomized Trial for Children and Young adults with Acute Lymphoblastic Leukemia (UKALL) 2011 protocol. Patients with febrile neutropenic (FN) episodes were treated with empirical antimicrobial therapy as per hospital guidelines. Patients ‘response to antimicrobial therapy, blood culture results and related complications were noted. Results: Out of a total 77 patients, 45 (58.4%) had 69 episodes of febrile neutropenia (FN), 62 (78.5%) episodes of febrile neutropenia (FN) were started empirical treatment with first-line antibiotics (piperacillin-tazobactam and amikacin) whereas 15 (21.7%) episodes of febrile neutropenia (FN) not responding to the 1st line were shifted to second-line antibiotics (meropenem and amikacin). Mean duration of fever was 4.1 ± 2.8 days on 1st line antibiotic regimen, 2.6 ± 1 days on 2nd line antibiotics and 6.3 ± 3.3 days on combination with antifungal drug. Ten patients received antifungal therapy empirically. Efficacy of the 1st line and the 2nd line was 72.5% and 77% respectively. Staphylococcus aureus was the most frequent organism isolated from blood culture results. During the induction phase, 10 (12.9%) patients..............